Surveillance for hepatocellular carcinoma in chronic viral hepatitis: Is it time to personalize it? - DEMİRTAŞ, COŞKUN ÖZER (BAISHIDENG PUBLISHING GROUP INC, 2021)
Surveillance with abdominal ultrasound with or without alpha-fetoprotein is recommended by clinical practice guidelines for patients who are considered to be at risk of developing hepatocellular carcinoma (HCC), including those with cirrhosis, advanced fibrosis and special subgroups of chronic hepatitis B (CHB). Application of the standard surveillance strategy to all patients with chronic liver disease (CLD) with or without cirrhosis imposes major sustainability and economic burdens on healthcare systems. Thus, a number of HCC risk scores were constructed, mainly from Asian cohorts, to stratify the HCC prediction in patients with CHB. Similarly, even if less than for CHB, a few scoring systems were developed for chronic hepatitis C patients or cirrhotic patients with CLD of different etiologies. Recently, a few newsworthy HCC-risk algorithms were developed for patients with cirrhosis using the combination of serologic HCC markers and clinical parameters. Overall, the HCC risk stratification appears at hand by several validated multiple score systems, but their optimal performance is obtained only in populations who show highly homogenous clinic-pathologic, epidemiologic, etiologic and therapeutic characteristics and this limitation poses a major drawback to their sustainable use in clinical practice. A better understanding of the dynamic process driving the progression from CLD to HCC derived from studies based on molecular approaches and genetics, epigenetics and liquid biopsy will enable the identification of new biomarkers to define the individual risk of HCC in the near future, with the possibility to achieve a real and cost/effective personalization of surveillance.
Keywords: Hepatocellular carcinoma; Surveillance; Chronic viral hepatitis; Risk score; Risk-stratification; Hepatitis B virus; Hepatitis C virus; GENOME-WIDE ASSOCIATION; PATIENTS RECEIVING ENTECAVIR; GROWTH-FACTOR GENE; HCC RISK SCORES; C VIRUS; B PATIENTS; SCORING SYSTEM; LIVER-DISEASE; FUNCTIONAL POLYMORPHISM; VIROLOGICAL RESPONSE